Analisis Peranan Alokasi Dana Terhadap Kinerja Keuangan Desa Melalui Aplikasi SISKEUDES - Najmud Dhafiq Ak , M.; Achmad , Erni; Rosmeli, Rosmeli (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This research aims: 1) To find out and analyze the condition of village fund allocation in Marga Manunggal Jaya Village, Sungai Bahar District, Muaro Jambi Regency during the 2016-2024 period, and 2) To find out and analyze the role of village fund allocation on village financial performance in Marga Manunggal Jaya Village, Sungai Bahar District via the Siskaudes application. In the analysis of village fund allocation data, this research applies data types, financial reports, allocation and village data, village revenues and village expenditure. And we took the data source directly from the Manungal Jaya Marga village office using the library research method. The results of the research show that 1) The average village fund allocation for Marga Manunggal Jaya during 2016-2024 increased by 3.87%. The contribution of Village Fund Allocation in Manunggal Jaya Village to village fund income was an average of 32.0%, if in A look at the effectiveness of the Village Fund Allocation in Manunggal Jaya Village shows that it has been effective. 2) Seen through the SIKEUDES application, the role of Village Fund Allocations on village financial performance is very good, because in planning, implementation, administration, reporting and accountability, village fund allocations are one of the budgets that are very influential in village financial performance, and with the existence of SISKEUDES Village financial management, especially village fund allocation, is more accurate and transparent.